MICROBIOLOGICAL AND RADIOLOGICAL IMPACTS THAT AFFECT WATER QUALITY AND VULNERABILITY IN HUMAN CONSUMPTION (REMUNOM, 2024)
Water is a primordial need for life, an indispensable natural resource for humans and other living beings, in addition to being an essential support for ecosystems. Used for human consumption and for socio-economic activities, it is taken from rivers, lakes, dams and aquifers, having a direct influence on health, quality of life and ear development. The study aims to carry out an integrative review regarding the microbiological and radiological parameters of drinking water for human consumption, as well as health safety regarding Social Assistance. From a bibliographic review in scientific databases, documents were read, categorized and critically analyzed.